2022
DOI: 10.1101/2022.05.21.22275413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared genetic etiology and causality between COVID-19 and venous thromboembolism: evidence from genome-wide cross trait analysis and bi-directional Mendelian randomization study

Abstract: Venous thromboembolism (VTE) occurs in up to one third patients with COVID-19. VTE and COVID-19 may share a common genetic architecture in etiology, which has not been comprehensively investigated. In this study, we leveraged summary-level data from the latest COVID-19 host genetics consortium and UK Biobank to study the genetic commonality between COVID-19 traits and VTE. We found a positive genetic correlation between COVID-19 hospitalization and VTE (rg = 0.2320, P-value= 0.0092). The cross-trait analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(159 reference statements)
0
3
0
Order By: Relevance
“…A 'leave one out' analysis was conducted to assess the in uence of individual SNPs on the exposure-outcome relationship, with a p-value over 0.05 signifying no horizontal pleiotropy [29] . To clarify whether the immune cell traits and RA genetically share the same genetic variant, we performed gene colocalization analysis [30] . To mitigate false positives in multiple testing, false discovery rate (FDR) correction was applied.…”
Section: Discussionmentioning
confidence: 99%
“…A 'leave one out' analysis was conducted to assess the in uence of individual SNPs on the exposure-outcome relationship, with a p-value over 0.05 signifying no horizontal pleiotropy [29] . To clarify whether the immune cell traits and RA genetically share the same genetic variant, we performed gene colocalization analysis [30] . To mitigate false positives in multiple testing, false discovery rate (FDR) correction was applied.…”
Section: Discussionmentioning
confidence: 99%
“…25 Interestingly, another preprint cross-trait analysis published by Huang et al found that VTE shared as many as eight and eleven genetic loci with severe SARS-CoV-2 infection and hospitalization for COVID-19, including genes participating to blood coagulation (e.g., ADAMTS-13 [a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13] and FV ). 26…”
Section: Tablementioning
confidence: 99%
“…25 Interestingly, another preprint cross-trait analysis published by Huang et al found that VTE shared as many as eight and eleven genetic loci with severe SARS-CoV-2 infection and hospitalization for COVID-19, including genes participating to blood coagulation (e.g., ADAMTS-13 [a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13] and FV). 26 The evidence emerged so far would hence persuade us that, perhaps, the most reasonable approach is not a matter of whether therapeutic-intensity anticoagulation may be "good" or "bad," "safe," or "dangerous," in patients with severe COVID-19 illness, but rather whether the correct answer to the original question could be… "depends." Straightforwardly applying here the concept of precision medicine, one would need to estimate the individual risk of developing venous thrombosis (i.e., as from elements summarized in ►Table 1), 27,28 that would then be balanced against the risk of bleeding.…”
mentioning
confidence: 99%